Kinetics and Adsorption Equilibrium Study of Free Fatty Acid (FFA) from Crude Palm Oil (CPO) on Anionic Resin - Sang Kompiang Wirawan; Daniel Timotius; Ivone Marselina Nugraha; Asdi Restana; Afrizal Luthfi Anggara; Sayoga Hidayatullah (Department of Chemical Engineering, Universitas Gadjah Mada, 2022)
Crude Palm Oil (CPO) is obtained from palm fruit extraction. Free Fatty Acid (FFA) level is one of the most important parameters to determine the CPO quality. The standard FFA level in the industry is less than 5%. In the palm oil processing industry, FFA levels in CPO have been minimized through vacuum distillation processes. However, due to the emulsified water in oil and long departure waiting time in port, FFA levels in CPO raise to above 5% resulting in lower quality and selling price. This study has developed a novel approach to mitigate this problem by using anionic resin as an adsorbent to decrease the FFA level. We investigated the kinetics and equilibrium behavior of FFA adsorption in CPO on the anionic resin. The adsorption was conducted in several resin dose (17.5%; 25%; 33.33%; 43%). The kinetic study shows that the FFA adsorption kinetics on anionic resin follows the Pseudo-second-order rate model with the value of k2 vary between 2.1034×10-4 – 1.7375×10-3 and the qe value is in the range of 103.627 - 163.880 (mg/g). The equilibrium study shows that the Freundlich isotherm model is the fittest. The Kf values are obtained between 4.16-15.02, and the n values are in the range of 1.62-2.05. The thermodynamic observation was also involved in this study. The value of and are 28.59 kJ/mol and 91.25 J/mol/K respectively. The results show that the reaction is endothermic, spontaneous, and feasible.